Transformation Theory as a Framework for Understanding Transformative Learning - Kokkos, Alexis (Adult Education Critical Issues, 2022)
Τhe first part of the present Introduction to Mezirow’s translated book outlines the formulation process of his theory, and the second Part presents its constituent components. The third part discusses the relationship between Transformation Theory and “transformative learning theory” and puts forward the opinion that the former constitutes a focal point of reference within the wider theoretical field of transformative learning, which includes diverse conceptualizations. In the last two parts, a reference is made to the book’s translation and suggestions are offered as to the creative and critical approach to its content.